Specific learning disability. (7th October 2018) - McDowell, Michael
Abstract: Specific learning disabilities (SLD) have an impact on discrete areas of academic function. They result in a level of difficulty that is unexpected when considered in the context of a student's overall intellectual and academic competence. A common example is dyslexia, an SLD that affects the acquisition of literacy. Medical professionals have an important role to play in the evaluation and management of SLD. The medical role is founded on the fact that these conditions are biologically based and have the potential to cause significant harm for the developing child. Even if details of biological causation are not possible to demonstrate for individual children, medical professionals may, nevertheless, make an important judgement call regarding the likelihood of aetiology. When learning problems are medically based, it is clearly unreasonable to expect children to do more than they are able and to learn faster than is reasonable. Advocacy around these biological presumptions and their implications is a major contribution to the well‐being of children who have SLD.